Screening of athletes for exercise-induced bronchoconstriction - Holzer, K.; Brukner, P. (Clinical Journal of Sport Medicine, 2004)
Exercise-induced bronchoconstriction (EIB) has a high prevalence in elite athletes, particularly endurance athletes, winter athletes and swimmers. Recent studies have shown that a clinical diagnosis of EIB has only a moderate sensitivity and specificity for EIB. This finding in conjunction with a recent ruling by the IOC-medical commission that all athletes competing in initially the 2003 Winter Olympic Games in Salt Lake City, and now the 2004 Summer Olympic Games in Athens require objective evidence of EIB, support the need for bronchial provocation challenge tests in the diagnosis of EIB. The recommended bronchial provocation challenge test is the eucapnic voluntary hyperpnea (EVH) challenge; this challenge test has been shown to have both a high sensitivity and specificity for EIB. Pharmacological challenge tests, such as the methacholine challenge test, have been shown to have only a low sensitivity but high specificity for EIB in elite athletes, and are thus not recommended in the athlete with pure EIB. Exercise challenge tests performed both in the laboratory and field have a high specificity for EIB; however those in the laboratory have only a moderate sensitivity for EIB in elite athletes, whilst those in the field are limited by problems with standardization. The osmotic challenge tests, such as the hypertonic saline and newer inhaled dry powder mannitol challenge have both a high sensitivity and specificity for EIB, and may be used as an alternative to the EVH challenge.